A comparison of ground settlement results with those predicted using Terzaghi and Asaoka methods / Zakiah Razak - Razak, Zakiah (2019)
Constructions on soft ground have often given rise to a number of critical geotechnical issues especially those related to ground settlements. Excessive post-construction settlements, which may be of total or differential nature, have always posed a serious problem to all parties concerned in the project. Insufficient knowledge of existing ground conditions due to, say, lacking a proper site investigation coupled with inadequate design; particularly in foundation are among the likely causes for the problem. For those critical cases settlement problem may lead to eventual failure of the structures constructed over it. The main objective of this study is to correlate and compare settlement results observed in the field with those theoretically predicted by Terzaghi’s (1996) one-dimensional consolidation theory method and Asaoka’s (1978) graphical plot approximate method which nevertheless relies on an “observational procedure” for settlement prediction. In addition, possible factors that can lead to the yielding of excessive settlement beneath housing property in Shah Alam of Selangor will also receive attention. Through appropriate tests conducted both in the laboratory and in the field the relevant properties of soils at site to facilitate subsequent research analysis were established and from these tests conducted the type of soil in the subgrade is identified to consist mainly of soft clay. To name a few of laboratory tests carried out are Particle Size Distribution, Atterberg Limits, Specific gravity Test and One-Dimensional Consolidation. For field tests conducted they are the Standard Penetration and Ground Water Level monitoring. Subsequently, based on soil properties obtained ground settlements were produced, one theoretically using Terzaghi’s method and the other assessed empirically via Asoka’s graphical solution. From the results obtained comparison among them were made where it revealed that settlements derived from Asaoka method is at least three times higher than that from Terzaghi’s. Perhaps it is worth mentioning that observations made during the course of study had shown clearly that the settlements occurred at site is considerable and after some careful consideration, it was thought that in the presence of very soft clay at site the exclusion of any suitable ground treatment method prior to construction is the main contributory factor for critical situation experienced at the site today. Furthermore, serious disturbance in the form of vibration imparted by major constructional activities in the vicinity of development site is thought would accentuate the already severe settlement problem there. In the current investigation, among one of the main objectives is to examine the usefulness of two potential methods, one being theoretical as in Terzaghi’s and the other semi-empirical of Asoka in arriving at a good estimation and thus prediction of ground settlement that might occur in the soft compressible subgrade layer especially during post-construction time. Subsequently, should such a settlement prediction tool be established then it will allow future engineer to have better chance of designing safer structures over soft ground through the adoption of preventive measures prior to construction and thus avoiding the development of excessive settlements during the post-construction years